Republic of Lithuania : Selected Issues. (IMF Staff Country Reports; Country Report, 2005)
This Selected Issues paper looks at short-term inflation dynamics in the new member states (NMS) of the European Union, focusing on the role of monetary policy regimes. It models the determinants of inflation in the NMS and assesses how different theoretical frameworks best fit the data. The paper investigates the macroeconomic performance of currency boards within the group of NMS, evaluates their role in reducing inflation, and identifies some of their distinctive characteristics. The paper also examines the current account sustainability for Lithuania.